The relation between social media dependency on cancer awareness and screening behaviour amongst B40 population in Malaysia / Ellysa Nabilah Abdul Halit, Ahlam Abdul Aziz and Shazleen Mohamed - Abdul Halit, Ellysa Nabilah; Abdul Aziz, Ahlam; Mohamed, Shazleen (Universiti Teknologi MARA, Perlis, 2024)
Social media has become a significant information source and its pervasive accessibility has transformed traditional health communication practices into health education, promotion, and behaviour change interventions. Individuals can develop a reliance on specific media platforms if they fulfil their information needs, and thus the need for cancer information. Unfortunately, low-income groups are often associated with lower cancer awareness and screening participation. However, social media has been proven to be advantageous in generating health messages to the targeted audience. Therefore, by adopting the Media Dependency Theory (MDT), this study aimed to investigate the relationship between social media in terms of social media dependency, perceived social media usefulness, social media trust towards cancer awareness and screening behaviour amongst the B40 population in Malaysia. The levels of cancer awareness amongst the B40 population will also be assessed. This study used purposive sampling to select participants from the B40 population in Klang Valley and obtain relevant information for the study objective. The data obtained were analysed by using descriptive statistics and inferential analysis. Findings revealed that all independent variables had a significant relation with cancer awareness and screening behaviour of the B40 population. This study was significant in understanding the use of social media in healthcare to increase cancer awareness and promote behaviour change amongst the population. The UITM Committee had approved ethical approval for ethics to conduct this study.